Antimicrobial activity of nudibranch Chromodoris lineolata associated bacteria against skin diseases pathogens from Jepara Coastal Waters, Indonesia - ALDI PRATAMA WIJAYA; AGUS SABDONO; MADA TRIANDALA SIBERO; AGUS TRIANTO; OCKY KARNA RADJASA (Society for Indonesian Biodiversity, 2022)
Abstract. Wijaya AP, Sabdono A, Sibero MT, Trianto A, Radjasa OK. 2022. Antimicrobial activity of nudibranch Chromodoris lineolata associated bacteria against skin diseases pathogens from Jepara Coastal Waters, Indonesia. Biodiversitas 23: 1911-1919. The emergence of multidrug-resistant (MDR) skin pathogens has caused the treatment of skin diseases to become increasingly ineffective using by conventional antibiotics. As a source of antimicrobial compounds against MDR pathogens, marine invertebrate-associated bacteria have been widely known for their valuable biological activity. Therefore, this study aims to determine the antimicrobial activity of nudibranch Chromodoris lineolata associated bacteria against various skin pathogens and to detect the presence of biosynthetic gene clusters (BGC) through a molecular approach. A total of 14 nudibranch-associated bacteria were successfully isolated from Awur Bay and Panjang Island. Antimicrobial activity screening using the agar plug method indicated that three bacterial strains showed antimicrobial activity against two skin pathogens, Propionibacterium acnes and Malassezia furfur. Based on the biochemical test, these potential strains were classified into the Terrabacteria and Proteobacteria groups. Through 16S rRNA gene sequencing, potential strains were identified as Streptomyces lateritius, Labrenzia marina, and Halomonas meridiana through 16S rRNA gene sequencing. The results of BGC detection showed the presence of a type II polyketide synthase (PKS II) biosynthetic gene cluster in Streptomyces lateritius and Labrenzia marina strains at 600bp-650bp.